Serum Interleukin-6, Interleukin-17A, and transforming growth factor beta are raised in systemic sclerosis with interstitial lung disease - Anupam Wakhlu; Rasmi Ranjan Sahoo; Jyoti Ranjan Parida; Mohit K Rai; Durga P Misra; Vinita Agrawal; Vikas Agarwal (Indian Journal of Rheumatology)
Background: Dysregulation in cytokines like interleukin-6 (IL-6), interleukin-17A (IL-17A) and transforming growth factor-beta (TGF β1) has been pathogenically implicated in systemic sclerosis (SSc). The present study aimed to assess their serum levels in patients with SSc and correlate with clinical manifestations. Methods: This cross-sectional, observational study included 93 patients fulfilling the 2013 revised ACR/EULAR SSc classification criteria and 33 age-and sex-matched healthy controls. Antinuclear antibody (ANA), extractable nuclear antigen (ENA) profile, chest radiograph, pulmonary function tests and electrocardiography were done. HRCT of thorax and echocardiography were done wherever indicated. Modified Rodnan skin score (MRSS) was calculated. Serum IL-6, IL-17A and TGF β1 levels were assayed using ELISA kit and compared among disease subtypes and clinical parameters. Spearman coefficient was used to test correlation between continuous variables. P value of <0.05 was considered significant. Results: The mean age of patients was 37.8+10.3 years (Female:Male: 30:1) with median duration of disease of 3 years. Serum IL-6, IL-17A and TGF β1 levels were significantly higher in patients as compared to controls (IL-6: 19.4±11 vs 6.7±3.9 pg/ml (P < 0.0001); IL-17A: 39.1±14.8 vs 16.4±2.1 pg/ml (P < 0.0001); TGF β1: 862.2±443 vs 377.2±208.8 pg/ml (P < 0.0001). Higher levels of these cytokines were also observed in patients of diffuse cutaneous SSc, those with lung fibrosis and anti-topoisomerase positivity. Conclusion: Serum IL-6, IL-17A and TGF β1 levels were significantly higher in SSc patients and higher levels were associated with ILD and skin fibrosis.